Is There a Community-Level Adaptation Deficit? - Ashwill, Maximillian; Heltberg, Rasmus (World Bank, Washington, DC, 2013)
This paper uses primary source data from several World Bank-led case studies on the “social dimensions of climate change” from 2008-2012 to understand how communities in developing countries can more successfully adapt to climate change. Poor communities face an adaptation deficit, specifically local communities, which engage more in coping measures than in adaptation measures, because the costs of adaptation remain too high while the effectiveness of adaptation in building resilience to severe weather events often remains limited or not sufficient in addressing long-term environmental trends. Further, adaptation can lead to negative outcomes, or maladaptation, which can occur when (1) planning does not sufficiently account for temporal and spatial factors, (2) policies contradict one another and create perverse incentives, (3) governance systems fail, and (4) communities lack the knowledge to adapt. Community leadership, organization, and trust towards nonlocal adaptation planners can build the social capital needed for collective action and successful adaptation.